The adoption factors of two-factors authentication in blockchain technology for banking and financial institutions - Amir Aizzat Basori; Nor Hapiza Mohd Ariffin (Institute of Advanced Engineering and Science, 2022)
Malaysian banks and financial organisations urgently require a secure authentication mechanism. However, there is a lack of research on the factors that drive blockchain authentication technology adoption, notably in Malaysian banks. This study identified the factors impacting adopting blockchain authentication technology in Malaysia. This document will be a roadmap for replacing existing technology utilizing the traditional transaction authorization code (TAC) via a short messaging service (SMS). In addition, this study looks into the elements that influence the new blockchain authentication technology's acceptability in Malaysia. The data was gathered from articles and research papers written by other scholars on blockchain authentication. To examine and categorise the aspects that influence the acceptance of blockchain authentication technology, we used risk management in technology (RMiT) standards to map them. Based on the result, security risk, regulatory support, technology latency, and technology complexity have been established as components of blockchain authentication adoption factors that can be a guideline to implement blockchain authentication in banking and financial institutions in Malaysia. In addition, the findings can contribute as a reference for future researchers to develop models or guidelines for blockchain authentication methods in banking and financial institutions.